Understanding the Influence of Rheology on Biofilm Adhesion and Implication for Food Safety - Adedola Adeboye; Helen Onyeaka; Zainab Al-Sharify; Nnabueze Nnaji (International Journal of Food Science)
Understanding biofilm rheology is crucial for industrial and domestic food safety practices. This comprehensive review addresses the knowledge gap on the rheology of biofilm. Specifically, the review explores the influence of fluid flow, shear stress, and substrate properties on the initiation, structure, and functionality of biofilms, as essential implications for food safety. The viscosity and shear-thinning characteristics of non-Newtonian fluids may impact the attachment and detachment dynamics of biofilms, influencing their stability and resilience under different flow conditions. The discussion spans multiple facets, including the role of extracellular polymeric substances (EPSs) in biofilm formation, the impact of rheological attributes of biofilm on their adhesion to surfaces, and the influence of shear forces between biofilms and substrate’s surface characteristics on biofilm stability. Analytical techniques, encompassing rheometry, microscopy, and molecular biology approaches, are scrutinized for their contributions to understanding these interactions. The paper delves into the implications for the food industry, highlighting potential risks associated with biofilm formation and proposing strategies for effective control and prevention. Future research directions and the integration of rheological considerations into food safety regulations are underscored as pivotal steps in mitigating biofilm-related risks. The synthesis of microbiology, materials science, and engineering perspectives offers a multidimensional exploration of rheology–biofilm interactions, laying the groundwork for informed interventions in diverse industrial settings.